Health-Related Physical Fitness is Associated with Total and Central Body Fat in Children Aged 6 to 10 Years - Gjonbalaj, Malsor; Morina, Besnik; Gontarev, Seryozha; Georgiev, Georgi (LLC OVS, 2022)
Study purpose. This study purpose was to investigate whether health-related physical fitness is associated with total and central body fat in school children aged 6–10 years. Materials and methods. A total of 2197 Macedonian children aged 6–10 years (1096 boys and 1101 girls) participated in the study. Health-related physical fitness was measured by the modified EUROFIT test battery: the 20 m shuttle run test (cardiorespiratory fitness); the handgrip strength test, the standing long jump and the 30 s sit-ups tests (muscular strength); the 4×10 m shuttle run test (motor fitness) and the sit and reach test (flexibility). Body mass index, body fat percentage and waist circumference were used as markers of total and central body fat, respectively. Results. The standing long jump, the 30 s sit-ups, the 4×10 m shuttle run and the 20 m shuttle run tests were negatively associated with all markers of total and central body fat in boys and girls after controlling for age (p<0.01). The handgrip strength test was positively associated with all markers of total and central body fat (p<0.01). No statistically significant correlation was established between the markers of total and central body fat and the sit and reach test. Conclusions. The present study broadens previous findings in children and adolescents which demonstrate correlations between the health-related physical fitness components, chiefly the muscle strength, the agility and cardiorespiratory fitness and total central adiposity. Fitness assessment should be introduced in future epidemiological and intervention studies in school children because it seems to be an important factor determining health.
Keywords: cardiorespiratory fitness, muscular strength, motor fitness, children, obesity